Development and validation of a parental social media mediation scale across child and parent samples. Issue 2 (7th January 2020) - Ho, Shirley; Lwin, May O.; Chen, Liang; Chen, Minyi
Abstract : Purpose: Social media use carries both opportunities and risks for children and adolescents. In order to reduce the negative impacts of social media on youth, the authors focus our efforts on parental mediation of social media. Specifically, the purpose of this paper is to enhance the conceptualization and operationalization of parental mediation of social media. Design/methodology/approach: First, the authors conducted focus groups with both children and parents in Singapore to categorize parental mediation strategies for social media and develop an initial scale of these strategies. Then, a survey was conducted with a nationally representative sample of 1, 424 child participants and 1, 206 parent participants in Singapore to develop and test the scale. Findings: The focus group results identified four conceptually distinct parental mediation strategies for social media, labeled as active mediation, restrictive mediation, authoritarian surveillance, and non-intrusive inspection, and were used to develop an initial scale of these strategies. Based on the data from survey questionnaires, the authors investigated both inter-item and item-total correlations and performed confirmatory factor analysis (CFA), which developed and validated the scale of parental mediation of social media. Originality/value: First, this research explained what parents do to manage children's social media use and identified four conceptually distinct parental mediation strategies of social media, making a significant contribution to the parental mediation theory. Additionally, the research developed the first theory-derived, successively validated and reliable scale in parental mediation of social media.